THE IMPACT OF POST-CONFLICT SECURITY SECTOR REFORM ON SOCIO-ECONOMIC DEVELOPMENT IN NIGERIA’S NIGER DELTA AND NORTH-EAST - Chibuzor Chile Nwobueze; Uchendu, Jennifer Matthew (International Journal of Business, Law and Political Science, 2026)
Objective: Nigeria’s Niger Delta and North-East represent two critical theatres of protracted conflict, rooted in resource grievances and violent extremism, respectively. Post-conflict stabilization efforts in both regions have heavily relied on security sector reform (SSR) designed to make the situation transition from militarized containment to sustainable, community-oriented peace. Method: Research revealed mixed but mainly constrained impact. Results:  Although SSR has secured some immediate dividends for the general reduction of violent visibility, the conversion of such security dividends into sustainable socio-economic development (SED) continues to be substantially impeded by institutional drivers. Disarmament, Demobilization and Reintegration (DDR) in the Niger Delta is counterproductive because the economy is not diversifying structurally away from oil and leads to cyclical grievance. Analogously, in the North-East, the link between the success of counter-insurgency operations and reconstruction is weak because the civilian-security relations have become fragmented, while the institutional adaptation to the human security needs of the region has been slow. This study found that SSR has not done great in making SED happen because they mainly focus on security. They often miss the bigger problems, like corruption in organizations, few people getting involved and communities not feeling like they own the process. Novelty: For SSR to become a true engine of socio-economic recovery, future interventions must be explicitly integrated with local governance reform and developmental planning, fundamentally linking security provision with the restoration of human capital and economic opportunity.